Community-Based Forest Management Strategy to Maintain Biodiversity in Papua - Imburi, Christian Soleman; Nugroho, Bambang; Renwarin, Dominggas M.H.; Anggrianto, Rusdi; Sutiharni, Sutiharni (West Science Nature and Technology, 2025)
This study explores the Community-Based Forest Management (CBFM) strategy as a means to maintain biodiversity in Papua, Indonesia. Using a qualitative approach, data were gathered through interviews with five key informants, including community leaders, local government officials, conservation NGO representatives, and researchers. Data analysis was conducted using NVivo software. The findings reveal that community participation, underpinned by indigenous practices, plays a critical role in forest conservation and biodiversity preservation. However, challenges such as limited resources, ambiguous land tenure systems, and external pressures hinder the effectiveness of these strategies. The integration of modern technology, such as GIS, was identified as a potential enhancer of CBFM outcomes, though capacity-building remains essential. This study underscores the importance of collaborative approaches, policy reforms, and capacity development in strengthening community-based conservation initiatives.